Determinants of Loss to Follow-Up Among MDR-TB Patients - Riadnin Maharja; Wahiduddin; Apik Indarti Moedjiono; Andi Zulkifli; Nur Nasry Noor; Hasanuddin Ishak; Rizky Maharja (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cases of tuberculosis has gotten worse since results of global surveillance revealed that mycobacterium isresistant to rifampicin and isoniazid. It can cause Loss to Follow-Up among MDR-TB patients. The purposeof this study is Determinants of Loss to Follow-Up among MDR-TB Patients. This research is an analyticobservational study with a case control study design with a retrospective approach. Cases were MDR-TBpatients who dropped out of treatment as much 27 people, while controls were subjects with MDR-TBpatients who did not Loss to Follow-Up of treatment as much 83 people. Data analysis was performedby looking at the Odds Ratio value. The result showed that knowledge (OR = 5.28, 95% CI = 1.410347–29.19908), drug side effect (OR = 32.324332, 95% CI = 4.732715–1353.07), family support (OR = 5.01875,95% CI = 1.602489 – 15.57846), social stigma (OR = 6.712963, 95% CI = 1.473798–61.68985) were thedeterminants of loss to follow up among MDR-TB patients. It can conclude that determinants of loss tofollow-up among MDR-TB patients include knowledge, drug side effects, family support, and social stigma.